Promotive Psychoeducational Poster-Based Intervention to Build a Supportive Psychological Climate in Special Needs School Communities - Fitriyah, Lailatul; Rokhmawan, Tristan (CV. Media Digital Publikasi Indonesia, 2025)
Special needs school environments represent communities with complex psychosocial dynamics, involving intensive and continuous interactions among children, parents, therapists, and educators. The complexity of children’s needs, parental expectations regarding developmental outcomes, and professional demands placed on therapists may contribute to emotional strain and disrupt the psychological well-being of the community. This Community Service program aimed to foster a more supportive psychological climate through a promotive intervention using psychoeducational posters. The program employed a Community-Based Participatory Research (CBPR) approach, beginning with a situational analysis conducted through individual and group interviews with parents and therapists to identify core community issues. The findings revealed difficulties in understanding children’s behavior as a form of needs communication, emotional strain experienced by therapists, and the lack of consistent psychoeducational media within the school environment. Based on these findings, psychoeducational posters were developed containing messages related to positive parenting, understanding children’s behavior, strengthening self-confidence, and self-care for caregivers. The posters were displayed in strategic shared spaces within the school community. This intervention functioned as a silent educator that encouraged reflection, enhanced psychological awareness, and strengthened shared understanding among community members. The findings suggest that promotive interventions using visual media can serve as an effective initial strategy for strengthening a supportive psychological climate in special needs school communities on a sustainable basis.